KESALAHAN GRAMATIKAL DALAM ABSTRAK SKRIPSI DARI LULUSAN FAKULTAS SASTRA - LANTENG, IRIANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT This research is entitled â€œKesalahan Gramatikal dalam Abstrak Skripsi dari lulusan Fakultas Sastraâ€ is an attempt to identify and analyze the kinds of errors in English made by graduates of the Faculty of Letters from the abstracts of their skripsi. The data were taken from the abstracts of the English graduatesâ€™ skripsi by visiting the library of Faculty of Letters Sam Ratulangi University. Ten abstracts were randomly selected from each publication year of 2006, 2007 and 2008 and used as the sample of this research. Elliâ€™s theory was used to explain how to analyze the grammatical errors made by these English Departmen graduates of the Faculty of Letters. The results of this research show that there are three kinds of errors made by students; omission (7 forms: plural â€“s, to be, article, suffix â€“ly, apostrophe s(â€˜s), suffix â€“ing, coordinating conjuction and) misinformation (5 forms: apostrophe ('), verb ending â€“ed, to be, Other, Direct and Indirect speech) misordering (2 forms: to be, subject-predicate) This research concludes there are still some errors contained in the abstract, in which the error of misinformation is the most error made by the graduates. This research contributes to the study of linguistics particularly in identifying errors that are commonly made by Indonesian learners of English. Â  Keyword: Grammatical errors, error analysis, omission, misinformation, misordering